Sátira e crítica social no romance Os tambores silenciosos, de Josué Guimarães - Seckler, Katia Luisa (2009)
This dissertation examines the novel Os tambores silenciosos (1977), by Josué Guimarães, and attemps to verify how the elements of the grotesque, the satire and carnivalization are used to construct the characters and the plot with the purpose of a critical representation of two critical historical periods corresponding with each other: the 1930 s and the contemporary construction of the text - the 1970 s. The censorship, the authoritarianism and the political repression are common to both periods. These aspects are dramatized in Os tambores silenciosos, which employs satirical elements and the construction of unusual situations that represent military and their arbitrary attitudes, flattering and weak politicians and violent policemen, denouncing the arbitrariness of a dictatorial regime. This work aims to highlight the grotesque, the carnivalization and the menippean satire, based on the Mikhail Bakhtin s theoretical formulations, in order to understand adequately the relations suggested by the presence of comic and unusual events in the novel under consideration.